2022
DOI: 10.3390/jpm12111893
|View full text |Cite
|
Sign up to set email alerts
|

Non-Surgical Transversal Dentoalveolar Compensation with Completely Customized Lingual Appliances versus Surgically Assisted Rapid Palatal Expansion in Adults—The Amount of Posterior Crossbite Correction

Abstract: The aim of this study was to compare the crossbite correction of a group (n = 43; f/m 19/24; mean age 27.6 ± 9.5 years) with surgically assisted rapid palatal expansion (SARPE) versus a non-surgical transversal dentoalveolar compensation (DC) group (n = 38; f/m 25/13; mean age 30.4 ± 12.9 years) with completely customized lingual appliances (CCLA). Arch width was measured on digital models at the canines (C), second premolars (P2), first molars (M1) and second molars (M2). Measurements were obtained before tre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…This is a follow-up study on DC-CCLA in comparison to SARPE. For the understanding of the work, the essential information is repeated here; specific details on the general study procedure can be found in the previous publication [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This is a follow-up study on DC-CCLA in comparison to SARPE. For the understanding of the work, the essential information is repeated here; specific details on the general study procedure can be found in the previous publication [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The measurements were taken at two timepoints: before treatment (T 0 ) and at T 1 , which was after debonding in the DC-CCLA group or after alignment in both jaws prior to a second surgical intervention for three-dimensional bite correction in the SARPE group. At T 1 , crossbite correction was completed in both groups, and two situations comparable for evaluation were present [ 29 ]. In the first study, the linear metric correction in the transverse plane was analyzed using reproducible landmarks [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations